Plasma heating and confinementat the GOL-3-II facility - Arzhannikov, A.V.; Astrelin, V.T.; Burdakov, A.V.; Ivanov, I.A.; Koidan, V.S.; Kuznetsov, S.A.; Mekler, K.I.; Novozhilov, S.A.; Polosatkin, S.V.; Postupaev, V.V.; Rovenskikh, A.F.; Savchkov, A.V.; et al. (Вопросы атомной науки и техники, 2000)
Results of experiments on plasma heating and confinement in multimirror open trap GOL-3-II are presented. This facility is intended for heating and confinement of a relatively dense (10¹⁵-10¹⁷ cm⁻³) plasma in axially-symmetrical magnetic system. The plasma heating is provided by a high-power electron beam (1 MeV, 30 kA, 8 µs, 200 kJ). Results of the experiments with multimirror configuration of the device indicate that the confinement time of the plasma with ne ~ (0,5÷5).10¹⁵ cm⁻³ and Te ~1 keV increases more than order of magnitude in comparison with single mirror device.